Evolving : the theory and processes of organic evolution - Ayala, Francisco Jose ([Menlo Park, Ca.] : Benjamin Cummings, 1979)
The purpose of this text is to provide an up-to-date account of the modern understanding of evolution for readers with only a high-school biology background, or its equivalent.
1. The evolution of evolutionary science -- 2. Basic genetics -- 3. Hereditary variation -- 4. Process of evolutionary change -- 5. Natural selection in action.
Includes bibliographical references and index.
Keywords: EVOLUTION